Language Change in British Parliamentary Discourse: A Corpus-Based Study of Power and Authority Markers, 1930-2005. - Soriano-Jiménez, Carlos (My University, 2024)
From a political perspective, 1928 marks the beginning of a new period in the history of democracy in the United Kingdom, once universal full suffrage was achieved via the Representation of the People Act. Taking into consideration this and other social and political factors, the main aim of the present project is to investigate how the process of democratisation influenced the language employed by the Members of Parliament between 1930 and 2005. For this purpose, we examine the use of markers of authority and power. Concretely, the evolution and the use of gender-neutral occupational titles are analysed. The corpus used for this investigation is the Hansard Corpus, which includes written records of British parliamentary debates.
Cambio lingüístico en el discurso parlamentario británico: un estudio basado en corpus de marcadores de autoridad y poder, 1930-2005
La revista Atlantis solo permite poner en el repositorio institucional la versión definitiva (publicada).
Keywords: Inglés - Aspectos sociales; Democratisation; Parliamentary discourse; Gender-neutral language; Authority; Power